(untitled) (Olhar de Professor, 2020)
In this article, we start from the recognition of centrality as the large-scale external assessments of learning assumed in educational policies in the last decades and are problematized in a relationship with a generic denomination of external evaluation, which are used in some cases and, in others, it’s not about evaluating learning. Then, limitations in the relationship with the current model are pointed out, mainly with regard to the involvement of teachers and elements that monitor or compose an external evaluation model of learning associated with teacher training in educational evaluation, highlighting as theories in evaluation validity and democratic evaluation. Finally, reports are presented of an experience in Mozambique similar to the proposed alternative model, with an appreciation of the conception, conditions and resources that an evaluation of learning, external or internal, should use as a support point for the success of all students. Keywords: learning assessment; external evaluation; educational politics